Ifrastructure of the third sector Republic of Kazakhstan: internal and external environment (The Journal of Psychology and Sociology, 2013)
In this article the internal and external environment of NGOs forming the infrastructure of the third sector. As follows from the basic provisions of organizational unity and mission-purpose organization determines the efficiency, professional-ism and team leaders.
Keywords: The third sector; infrastructure of the third sector; internal environment NGOs; external environment NGOs